EFEKTIVITAS PENGGUNAAN MEDIA POWERPOINT DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENERAPAN KONSEP MUTU HASIL PERTANIAN - Salmiah, Salmiah; Fatah, Anwar; Purnamawati, Purnamawati (Universitas Negeri Makassar, 2016)
This is class action research which aimed to improve the student’s achievement in plant aplication concept quality of agricultural at the X class in SMK Negeri 3 TPHP Takalar. The subjects of this research consisted of 21 student’s. Recearch procedure includes planning implementation, observations and reflection. The data that has been collected; is analyzed using quantitative and qualitative data. Based on the result of the research, it can be concluded that the aplication of Powerpoint media can improve the student’s achievement. The result of the pre-cycle, cycle I and cycle II that has a significant improvement